Masjid Menjadi Ruang Sinergi Pendidikan dan Pelatihan Bagi Masyarakat Modern - Dwi Yana Alidia; Firly Fadila Julita; Saskia Azhara Putri; Reni Ramita Sari; Wismanto Wismanto (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
The mosque has an important role as a center for education and training in modern society. In the digital age, mosques can offer a variety of relevant formal and non-formal education programs. The role of the mosque in educating young people including teaching good moral values. The mosque is also a forum for communication and interaction between community members, creating collaboration in learning. This article aims to increase the understanding of the role of the mosque, integrate education, encourage community involvement and foster social interaction. his article uses a literature review method (Literature Review) by collecting data and sources related to a particular topic which is obtained from various sources such as journals, research reports, and other library sources. The results showed that the mosque could function as an educational and training synergy space that played an important role in the development of human resources. The development of a fast era. In this digital era, the mosque can adapt by offering various relevant educational programs, both in the form of formal and non-formal education.